2006
DOI: 10.1074/jbc.m508998200
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Overexpression of Sarcolipin in the Mouse Heart Decreases Sarcoplasmic Reticulum Calcium Transport and Cardiac Contractility

Abstract: The role of sarcolipin (SLN) in cardiac physiology was critically evaluated by generating a transgenic (TG) mouse model in which the SLN to sarco(endoplasmic)reticulum (SR) Ca 2؉ ATPase (SERCA) ratio was increased in the ventricle. Overexpression of SLN decreases SR calcium transport function and results in decreased calcium transient amplitude and rate of relaxation. SLN TG hearts exhibit a significant decrease in rates of contraction and relaxation when assessed by ex vivo work-performing heart preparations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 31 publications
3
82
1
Order By: Relevance
“…Both PLB and SLN inhibit SERCA activity in the heart by lowering the apparent calcium affinity of the pump [42,46,47]. The inhibitory effect of SLN is relieved upon β-adrenergic stimulation, as observed for PLB [13,[46][47][48]. Although, PLB and SLN inhibit SERCA2a activity, there might be subtle but important differences in their mechanism of regulation.…”
Section: Sln Functionally Differs From Plbmentioning
confidence: 94%
See 3 more Smart Citations
“…Both PLB and SLN inhibit SERCA activity in the heart by lowering the apparent calcium affinity of the pump [42,46,47]. The inhibitory effect of SLN is relieved upon β-adrenergic stimulation, as observed for PLB [13,[46][47][48]. Although, PLB and SLN inhibit SERCA2a activity, there might be subtle but important differences in their mechanism of regulation.…”
Section: Sln Functionally Differs From Plbmentioning
confidence: 94%
“…Although, PLB and SLN inhibit SERCA2a activity, there might be subtle but important differences in their mechanism of regulation. For example, as illustrated in Figure 3, the inhibitory effect of PLB on SERCA2a is relieved at high calcium concentrations [42], whereas the inhibitory effect of SLN on SERCA2a is observed even at high calcium [46,47]. These functional differences could be attributed to the structural differences in the lumenal domains (C-terminus) of the two proteins.…”
Section: Sln Functionally Differs From Plbmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, however, the role of SLN in cardiac physiology was investigated using transgenic mouse models (11,12). Specifically, it was found that the overexpression of SLN affects calcium transport on the sarco(endo)plasmic reticulum, decreasing the amplitude of the calcium transient and the rate of muscle relaxation (11).…”
mentioning
confidence: 99%